EFFECT BRIGHTNESS COLOR GUPPY FISH (Poecilia reticulata) - soedibya, petrus; Gultom, Noris; Marnani, Sri; Muslih, Muslih; Fitriadi, Ren (Journal Of Artha Biological Engineering, 2024)
Guppy fish (Poecilia reticulata) is a popular ornamental fish because of their unique color patterns, the color of ornamental fish will fade if their feed does not contain enough pigmentation to keep them bright. This study aimed to determine the effect of adding Spirulina sp. powder with different dosage to the feed on the color brightness of guppy fish. This study used a completely randomized design (CRD) with five treatments (feed added with Spirulina sp. powder as much as 0%, 0.3%, 0.6%, 0.9%, and 1.2%) and three replications. The test fish were male HB Red guppy fish with a size of 3 cm and a density of 3 fish/aquarium. Water changes (siphoning) was done every morning, and feeding was done twice a day. The parameters observed in this study were the chroma value, survival rate, and water quality. The result showed that the effect of adding Spirulina sp. powder to the feed at a dose of 0.9% and 1.2% had a significant effect on the color brightness. The survival rate indicates that the outcomes were not significantly different between treatments from a 100% success rate. The adding of Spirulina sp. powder increases the brightness of Guppy fish. The brightness color is very important in the Guppy fish farming, because color is the main indicator in ornamental fish. The water has a good quality, with an average temperature of 25.8-26°C and a pH of 7.9-8.0.